SARCASM FOUND ON THE 1975’S INSTAGRAM COMMENT SECTION - Muzakkir, Elza Awalia; Weda, Sukardi (Faculty of Languages and Literature, Universitas Negeri Makassar, 2025)
Due to the variety of circles, both good and bad comments which sometimes contain sarcasm are easily found on social media. People frequently employ sarcasm to make fun of others by interpreting reality in a different way. Sarcasm enables speakers to highlight how disturbed they are about a subject or situation rather than simply stating that they are irritated or furious. Examining the types of sarcasm on the1975’s Instagram comment section under several posts and to know which kind of sarcasm receives the most engagement. Qualitative descriptive is applied as a method in this study. The data is taken from the comment section under several posts of the1975 on Instagram. Sarcasm types are divided into four types; proposition, lexical, like-prefixed, and illocutionary sarcasm. We found 32 sarcasm data. This study concludes that all types of sarcasm were found in the1975 Instagram comment section, such as 17 illocutionary sarcasm, six propositional sarcasm, five lexical sarcasm, and finally like-prefixed sarcasm. Illocutionary sarcasm received the most engagement.